If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(x + 2) = (x + 3)(5x + 1) Reorder the terms: (3 + x)(x + 2) = (x + 3)(5x + 1) Reorder the terms: (3 + x)(2 + x) = (x + 3)(5x + 1) Multiply (3 + x) * (2 + x) (3(2 + x) + x(2 + x)) = (x + 3)(5x + 1) ((2 * 3 + x * 3) + x(2 + x)) = (x + 3)(5x + 1) ((6 + 3x) + x(2 + x)) = (x + 3)(5x + 1) (6 + 3x + (2 * x + x * x)) = (x + 3)(5x + 1) (6 + 3x + (2x + x2)) = (x + 3)(5x + 1) Combine like terms: 3x + 2x = 5x (6 + 5x + x2) = (x + 3)(5x + 1) Reorder the terms: 6 + 5x + x2 = (3 + x)(5x + 1) Reorder the terms: 6 + 5x + x2 = (3 + x)(1 + 5x) Multiply (3 + x) * (1 + 5x) 6 + 5x + x2 = (3(1 + 5x) + x(1 + 5x)) 6 + 5x + x2 = ((1 * 3 + 5x * 3) + x(1 + 5x)) 6 + 5x + x2 = ((3 + 15x) + x(1 + 5x)) 6 + 5x + x2 = (3 + 15x + (1 * x + 5x * x)) 6 + 5x + x2 = (3 + 15x + (1x + 5x2)) Combine like terms: 15x + 1x = 16x 6 + 5x + x2 = (3 + 16x + 5x2) Solving 6 + 5x + x2 = 3 + 16x + 5x2 Solving for variable 'x'. Reorder the terms: 6 + -3 + 5x + -16x + x2 + -5x2 = 3 + 16x + 5x2 + -3 + -16x + -5x2 Combine like terms: 6 + -3 = 3 3 + 5x + -16x + x2 + -5x2 = 3 + 16x + 5x2 + -3 + -16x + -5x2 Combine like terms: 5x + -16x = -11x 3 + -11x + x2 + -5x2 = 3 + 16x + 5x2 + -3 + -16x + -5x2 Combine like terms: x2 + -5x2 = -4x2 3 + -11x + -4x2 = 3 + 16x + 5x2 + -3 + -16x + -5x2 Reorder the terms: 3 + -11x + -4x2 = 3 + -3 + 16x + -16x + 5x2 + -5x2 Combine like terms: 3 + -3 = 0 3 + -11x + -4x2 = 0 + 16x + -16x + 5x2 + -5x2 3 + -11x + -4x2 = 16x + -16x + 5x2 + -5x2 Combine like terms: 16x + -16x = 0 3 + -11x + -4x2 = 0 + 5x2 + -5x2 3 + -11x + -4x2 = 5x2 + -5x2 Combine like terms: 5x2 + -5x2 = 0 3 + -11x + -4x2 = 0 Factor a trinomial. (1 + -4x)(3 + x) = 0Subproblem 1
Set the factor '(1 + -4x)' equal to zero and attempt to solve: Simplifying 1 + -4x = 0 Solving 1 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -4x = 0 + -1 -4x = 0 + -1 Combine like terms: 0 + -1 = -1 -4x = -1 Divide each side by '-4'. x = 0.25 Simplifying x = 0.25Subproblem 2
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Solution
x = {0.25, -3}
| 3/5x6 | | 3/35x6 | | 55A^2+28A-3= | | 4.9=n+-2.6 | | r^4+2r^3+r^2+8*r-12=0 | | 4x+14=-22-2x | | 21=-4+9(y+8) | | 6x+y=50 | | 7*2=z*2/2 | | 3(-2)-1.2y=-2.4 | | r^4+2r^3+r^2+8r-12=0 | | 2(8-c)=-2 | | 66-2x=10-10x | | 17.5=32t-16tsquared | | 8-m=4 | | 8x-5=180 | | 20-g=13 | | 7x-103=3x-7 | | 3x+2=28-(3x+2) | | 3x-1.2(2)=-2.4 | | 12+f=16 | | 5+12x=-6+x | | t=60+16t-t^2 | | 3mx-5=7m-2x | | 10+e=13 | | -5-4a+5a=7 | | -8(b-3)=-24+4b | | c+10=12 | | 2x/3-58-2x | | .5x+6=x-4 | | 82+9x-6+6x-1=180 | | 25-5x=-13-8x |